The Association between Mental Health Literacy and Perception of Community Stigma with Help-Seeking Behavior among Final Year University Students - Mardliyyah, Khonsa'; Asyanti, Setia (Universitas Muhammadiyah Surakarta, 2022)
The responsibilities and demands of senior students during their final year of study before becoming a graduate lead to anxiety, stress, and even depression. This situation makes senior students need the help of others to overcome their problems. The purpose of this research is to examine the relationship between mental health literacy and perception of community stigma with the help-seeking behavior of senior students. The research design used is a correlational quantitative method. The research subjects are 218 senior students at Muhammadiyah University Surakarta. The sampling technique used is incidental sampling. Data were collected using mental health literacy scales, perception of community stigma scales, and help-seeking behavior scales. Data analysis techniques used multiple linear regression tests with SPSS 25 for Windows. The results showed that mental health literacy and perception of community stigma together significantly influenced helpseeking behavior (F = 10.623, p < 0.05). Mental health literacy significantly and positively influenced help-seeking behavior (t = 2.030, p < 0.05), while perception of community stigma significantly and negatively influenced help-seeking behavior (t = -3.833, p < 0.05). The contribution of mental health literacy and perception of community stigma to help-seeking behavior was R² = 0.09 (9%).